A practical guide to the handling and administration of personalized transcriptionally attenuated oncolytic adenoviruses (PTAVs). (2nd September 2018) - Larson, Christopher; Oronsky, Bryan; Varner, Gina; Caroen, Scott; Burbano, Erica; Insel, Elisa; Hedjran, Farah; Carter, Corey A.; Reid, Tony R.
ABSTRACT: The aim of this review is to provide practical information on the handling, storage, and administration procedures for personalized oncolytic adenoviruses (PTAVs), which have recently entered clinical trials. As described herein, personalized oncolytic viruses refer to transcriptionally attenuated (TA) type 5 adenoviruses that are engineered to carry one or more neoantigenic transgenes derived from patient tumors. Vials of personalized viruses should be stored at −60°C without refreezing after thawing to maintain infectivity. To prevent accidental exposure and transmission, full implementation of universal precautions for preparation, administration, and handling is required. Contaminated materials that come into contact with personalized viruses should be properly disposed of in accordance with local institutional procedures. Severely immunocompromised or pregnant healthcare workers should not prepare or administer personalized viruses or directly contact injection sites. Personalized viruses are administered subcutaneously and intratumorally; however, only subcutaneous injection will be considered in this review. The specific storage, handling, administration, and safety requirements for personalized viruses are easily managed in the context of a clinical trial following the directives from the study protocol.